VARIATION OF C/N RATIO AND FERMENTATION TIME IN RESPONSE SURFACE METHODOLOGY FOR CELLULASE PRODUCTION FROM Bacillus sp. BPPT CC RK2 - MISRI GOZAN; AGUNG MARSSADA BIORATA; SISWA SETYAHADI (International Journal of Pharma and Bio Sciences, 2013)
This study aimed to obtain optimum operating conditions in the production of cellulase by Response Surface Methodology using Bacillus sp. BPPT CC RK 2. This optimization used natural substrate that was cheap and widely available in Indonesia. This substance was also a source of carbon and nitrogen for the production of cellulose enzymes. These carbon and nitrogen sources are the emerging substance to replace carboxylmethyl (carbon source) and yeast extract (source of nitrogen) that are still expensive. The research was conducted in four stages, namely: (1) the manufacture and the selection of medium composition ; (2)enzyme production through fermentation; (3) the use of Response Surface Methodology using a software design expert in determining the optimum point of cellulase; (4) and the enzyme activity test. The results showed that the isolates Bacillus sp. CC BPPT optimum RK 2 produce cellulase for 12 hours in media with concentrations of rice bran 50% (w/v), and coconut water concentration of 20% (v/v).